A diving physician's experience of dental barotrauma during hyperbaric chamber exposure: case report - ALTUN, BÜŞRA DİLARA; DUMLU, ASIM (My University, 2022)
Previous cases of dental barotrauma have been reported in pilots and divers. We report a case of dental barotrauma and barodontalgia in a diving physician accompanying patients during hyperbaric oxygen treatment, and due to pressure changes in the hyperbaric chamber. The physician developed sharp pain localised to the right maxillary molars but radiating to the face, ear and head during decompression from 243 kPa (2.4 atmospheres absolute). The pain intensified following completion of decompression and was consistent with irreversible pulpitis. Clinical examination and panoramic radiography suggested fracture of a heavily restored tooth due to barotrauma. This was managed by tooth extraction. The physician subsequently discontinued accompanying the patients during their hyperbaric oxygen treatment sessions. Dentists and maxillofacial surgery specialists suggest waiting for a minimum of four weeks or until the tooth socket and/or oral tissue has healed sufficiently to minimise the risk of infection or further trauma before exposure to further pressure change. Although seemingly rare, and despite the comparatively slow pressure changes, dental barotrauma can occur in hyperbaric chamber occupants.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Safety Research; General Social Sciences; Health (social science); Public Health, Environmental and Occupational Health; Occupational Therapy; Epidemiology; Social Sciences & Humanities; Health Sciences; Barodontalgia; Case reports; Hyperbaric oxygen treatment; Pain; OXYGEN THERAPY; BARODONTALGIA; DENTISTRY; FRACTURE